The onset of polymorphonuclear leucocyte membrane-stimulated metabolic activity. - Williams, A J (1981)
The time course of polymorphonuclear leucocyte oxidative metabolism following membrane stimulation by four different agents was examined using the techniques of luminol- and lucigenin-dependent chemiluminescence. After addition of opsonized zymosan, phorbol myristate acetate or digitonin to polymorphonuclear leucocytes there was a lag period of between 35 and 55 sec before the onset of chemiluminiscence. In contrast, after addition of the chemotactic peptide N-formyl-methionyl-leucyl-phenylalanine (FMLP), the lag period before chemiluminescence was less than 19 sec. Luminol-dependent chemiluminescence was reduced by superoxide dismutase and almost abolished by sodium azide. The inhibitory effect of the latter was less marked when using FMLP. Lucigenin-dependent chemiluminescence was inhibited by superoxide dismutase and enhanced by sodium azide. Cytochalasin B reduced zymosan and digitonin stimulated chemiluminescence but increased FMLP stimulated chemiluminescence. The results of the onset of polymorphonuclear leucocyte metabolic activity using other techniques.